The Transcrustal Magma Reservoir Beneath Soufrière Hills Volcano, Montserrat: Insights From 3‐D Geodetic Inversions. Issue 20 (17th October 2020) - Gottsmann, J.; Flynn, M.; Hickey, J.
Abstract: We invert intraeruptive ground displacements recorded between 2003 and 2005 on Montserrat to shed light on the magmatic plumbing system of Soufrière Hills Volcano. Incorporating 3‐dimensional crustal mechanical and topographic data in a finite‐element model, we show that the recorded displacements are best explained by a southeastward dipping (plunge angle of 9.3°) vertically extended triaxial ellipsoidal pressure source with semiaxes lengths of 1.9 and 2.0 km horizontally, and 5.0 km vertically. The source is centered at 9.35 km depth below main sea level and embedded in independently imaged anomalously weak crustal rocks. The source orientation appears to be controlled by the local stress field at the intersection of two major WNW‐ESE and NW‐SE striking tectonic lineaments. We derive an average volumetric strain rate of 8.4 × 10 −12 s −1 by transcrustal pressurization which may have contributed to flank instability and mass wasting events in the southern and eastern sectors of the island. Key Points: First 3‐D numerical inversion of surface displacements for Soufrière Hills Volcano highlights strong volcano‐tectonic interactions Surface strains are controlled by topography and crustal mechanical heterogeneity Transcrustal magmatic system is imaged by SE‐ward dipping triaxial ellipsoid